Friction stir welding of high strength 7XXX aluminum alloys - Mishra, Rajiv S.; Komarasamy, Mageshwari (Butterworth-Heinemann is an imprint of Elsevier, 2016)
Annotation
Keywords: TECHNOLOGY & ENGINEERING / Technical & Manufacturing Industries & Trades; Friction stir welding